CHOREOGRAPHIC TRANSFORMATION IN ZAPIN KASIH: A STUDY OF MOVEMENT MOTIFS THROUGH ALMA HAWKINS' CREATIVE PROCESS: CHOREOGRAPHIC TRANSFORMATION IN ZAPIN KASIH: A STUDY OF MOVEMENT MOTIFS THROUGH ALMA HAWKINS' CREATIVE PROCESS - Heniwaty, Yusnizar; DN, Rr. Ruth Hertami DN; Rahmah, Sitti (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study examines the creation process of the Zapin Kasih dance choreography through thetheoretical lens of Alma Hawkins' creative stages. The research aims to identify how exploration,improvisation, composition, and evaluation operate as creative strategies in developing traditionalZapin movements into innovative choreographic forms. Using qualitative artistic research methods,data were collected through rehearsal observations, interviews with choreographer YusnizarHeniwati, and performance documentation. The results indicate that Hawkins' framework effectivelysupports the transformation of traditional Zapin vocabulary—tahto, langkah dua, alif, and menitibatang —into six new movement motifs. Each stage of the creative process reflects different layersof artistic decision-making: exploration of cultural symbols ( sarongs ), improvisation of bodilyresponses, composition of rhythmic sequences, and evaluation of aesthetic and cultural coherence.These findings suggest that Hawkins' theory not only guides artistic creation but also mediatesbetween heritage preservation and contemporary innovation. This study contributes to theunderstanding of practice-as-research methodology in dance, particularly in the context oftraditional Southeast Asian arts, where choreography functions as both an artistic output and acultural inquiry.